1980
DOI: 10.1111/j.1460-2466.1980.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Watches Public Television?

Abstract: H o m e r it has been measured, the projik of the audience for public TV has t u d out to be a well-educated, afluent minority.One of the difficulties in writing about the audience for public television is that it is so small.' Another difficulty is due to the fact that public television is a decentralized cluster of local stations which do not necessarily share programming philosophies. Some stations, especially those in the large urban markets, are interested in attracting large and loyal audiences, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The U.S. public broadcasting system came of age during the presidency of Lyndon B. Johnson and was passed by Congress in 1967 as an extension of Great Society programs. While officially presented as a vehicle to bring quality, diversity, and public interest goals to all Americans, the servicewith the key exception of children's programs-became a channel for the professional middle class (Lyle 1975;Statistical Research 1974;LeRoy 1980). Conceived against the grain of the "vast wasteland," U.S. public television did not solicit public involvement (Rowland 1976(Rowland , 1986, nor was the service intended to provide widely viewed news and entertainment.…”
Section: Public Broadcasting Service (Pbs) Versus the "Vast Wasteland"mentioning
confidence: 99%
See 1 more Smart Citation
“…The U.S. public broadcasting system came of age during the presidency of Lyndon B. Johnson and was passed by Congress in 1967 as an extension of Great Society programs. While officially presented as a vehicle to bring quality, diversity, and public interest goals to all Americans, the servicewith the key exception of children's programs-became a channel for the professional middle class (Lyle 1975;Statistical Research 1974;LeRoy 1980). Conceived against the grain of the "vast wasteland," U.S. public television did not solicit public involvement (Rowland 1976(Rowland , 1986, nor was the service intended to provide widely viewed news and entertainment.…”
Section: Public Broadcasting Service (Pbs) Versus the "Vast Wasteland"mentioning
confidence: 99%
“…While PBS claims to reach a cross section of the U.S. population (Public Broadcasting Service 1995a), audience research has consistently shown that its core adult viewership is small, well-educated, and above average in socioeconomic status (LeRoy 1980;Public Broadcasting Service 1990a, 1990b, 1995b. The cultural aura that surrounds public television, coupled with its programming priorities, has also limited the service's multicultural policy goals.…”
Section: People Like Who?mentioning
confidence: 99%